2020
DOI: 10.1007/978-3-030-32835-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Using the TUNGSTEN Approach to Co-design DataDay: A Self-management App for Dementia

Abstract: User expertise illuminates people's motivations for using technology (Hassenzahl 2011), including the reasons that they do or do not use applications, devices and services. Identifying user's priorities aligns with the current or 'third wave' of HCI, which embraces the experience and meaning-making of the technology user(s) (Bødker 2015). When working with people living with dementia, expertise from families can also deepen one's understanding of potential users' motivations for and challenges experienced when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Clinical, research, and e-learning staff observed the participants as they engaged in the modules, paying special attention to their reactions and noting any areas of confusion and particular enjoyability. Participants filled out feedback questionnaires (The Scavenger Hunt measure from the TUNSGTEN tools: http://tung sten-training.com) for each module that assessed usability of new technologies in interactive settings by indicating yes or no to the following statements: (a) This is easy to use, (b) This is something I would use, and (c) This is something I enjoy (Astell, Dove, Morland, & Donovan, 2020). The questionnaire also encouraged participants to add general comments or suggestions for improvement, to enable technologies to be modified to better meet the user's needs.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Clinical, research, and e-learning staff observed the participants as they engaged in the modules, paying special attention to their reactions and noting any areas of confusion and particular enjoyability. Participants filled out feedback questionnaires (The Scavenger Hunt measure from the TUNSGTEN tools: http://tung sten-training.com) for each module that assessed usability of new technologies in interactive settings by indicating yes or no to the following statements: (a) This is easy to use, (b) This is something I would use, and (c) This is something I enjoy (Astell, Dove, Morland, & Donovan, 2020). The questionnaire also encouraged participants to add general comments or suggestions for improvement, to enable technologies to be modified to better meet the user's needs.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…This 4-h long workshop was designed to provide an inclusive environment where everyone’s voice could be heard. Two interactive activities – Technology Interaction ( Astell et al, 2020 ) and Scavenger Hunt ( Astell et al, 2020 ) – were combined with student presentations on the three THAW projects. Activity descriptions, materials and aims are set out in Table 1 .…”
Section: Workhop One ‘Mental Wellbeing: Can Technology Help Older People Lead a Healthier And Happier Life?’mentioning
confidence: 99%
“…Building on the success and lessons learnt from the first workshop, activities were designed to facilitate discussion and thinking about ways of using new technology to support mental wellbeing in later life within services. This second workshop lasted 5.5 h and included three interactive activities: Vignettes ( McGrath et al, 2016 ), Scavenger Hunt ( Astell et al, 2020 ), and Invention Test ( McGrath et al, 2016 ). These are detailed in Table 2 .…”
Section: Workhop Two: ‘Healthy Aging Within Your Reach: Shaping New Technologies To Support Mental Wellbeing For Older People’mentioning
confidence: 99%
“…AGE-WELL has supported the development of TUNGSTEN tools, a set of interactive activities to foster co-production. TUNGSTEN tools have been used to explore the role of technology in late-life mental health, 32 co-production of a self-management app for people newly diagnosed with dementia, 33 agile development of an on-line memory intervention program for healthy older adults, 34 and a framework for evaluating technology to manage chronic pain. 35 These freely available tools plus case studies and guidance for organizing co-production sessions and workshops can be found on the TUNGSTEN website: http://tungsten-training.com.…”
Section: Introductionmentioning
confidence: 99%